Legal Protection of Patients and Responsibilities of Artificial Intelligence-Based Telemedicine Health Services in Indonesia - Alvina Alvina; Markoni Markoni; I Made Kanthika; Dyah Permata Budi Asri (Green Publisher Indonesia, 2025)
The advancement of digital technology in healthcare has fostered the emergence of telemedicine powered by artificial intelligence (AI), particularly within medical practice. In Indonesia, however, this rapid development has not been matched by clear legal safeguards for either patients or medical professionals. The central issues concern the extent of patient protection and the allocation of liability when errors occur in AI-assisted telemedicine services. This study employs a normative juridical approach, supported by statutory analysis, conceptual inquiry, and comparative legal study. The findings reveal that Indonesia’s health regulations remain general in nature and do not specifically define liability boundaries in AI-based medical practice. The absence of a lex specialis and ambiguity regarding legal subjects create potential injustice. This article recommends establishing regulations grounded in precautionary principles, incorporating algorithmic safety, independent audits, and a shared liability framework among physicians, platform providers, and developers to ensure accountability and patient protection in digital healthcare.